The Comprehensive Systematic Review of Effectiveness of Salicylic Acid in Chemical Peeling Procedures for Comedonal Acne - Auliani Deby Veronica; Deriel Elka Hidayat (International Medical Journal Corp. Ltd, 2026)
Background: Comedonal acne is characterized by open and closed comedones and often requires effective keratolytic agents. Salicylic acid (SA), a lipophilic beta-hydroxy acid, is widely used in chemical peels, but comprehensive systematic evidence focusing specifically on comedonal outcomes is limited. Methods: This systematic review analyzed 52 studies, including randomized controlled trials, and comparative cohort studies. The primary outcome was comedone-specific reduction following SA chemical peels. Secondary outcomes included overall acne improvement, safety, tolerability, and comparison with other peeling agents. Results: Six biweekly sessions of 30% SA peels achieved consistent comedone reductions of 88–90% (p<0.001) (1,2). The salicylic-mandelic acid combination (20% SA + 10% mandelic acid) produced 90.2% comedonal clearance, significantly superior to 35% glycolic acid (35.87%) (5). SA 30% was significantly more effective than Jessner’s solution for non-inflammatory lesions (p=0.04) (4) and superior to 25% TCA in one study (69% vs. 60% reduction, p<0.001) (11), though another found equivalence (6). Combination therapies enhanced outcomes: SA peel plus pulsed dye laser showed greater improvement than SA alone (p=0.003) (7); adding SA peels to oral isotretinoin increased clearance from 73.4% to 92.5% (9). Safety was favorable: transient burning and erythema were common but self-limiting; no serious adverse events were reported. SA peels showed better tolerability than TCA and mandelic acid peels (6,16,40). Discussion: The lipophilic property of SA enables deep follicular penetration, explaining its superior comedolytic effect. Protocol variations (session frequency, outcome measurement) explain the reported heterogeneity (54–90%). The 6-session biweekly regimen appears optimal. Conclusion: Thirty percent salicylic acid peels administered biweekly for six sessions are highly effective, safe, and well-tolerated for comedonal acne, achieving approximately 90% comedone reduction. SA is superior or equivalent to most superficial peeling agents for comedones.